2012
DOI: 10.1111/j.1467-9841.2012.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Voice quality as a marker of ethnicity in New Zealand: From acoustics to perception1

Abstract: This study is the first acoustic analysis of voice quality in the two main ethnic dialects of New Zealand English. In a production experiment, narratives from 36 speakers were analyzed and H1‐H2 spectral tilt measures were calculated for each vowel. The results provide instrumental evidence for impressionistic claims about the differing voice quality features of the two main ethnic groups, showing that Maori English speakers are creakier than European New Zealanders. A perception experiment was also carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Linguistic experience also plays a role in the perception of ethnic varieties. In the New Zealand context, for example, high previous exposure to the Māori English variety has been shown to have a beneficial effect on perception and accuracy in ethnolect identification tasks even when listeners only have access to suprasegmental information in the speech signal, such as rhythm (Szakay, 2008a), intonation (Szakay, 2008b), and voice quality (Szakay, 2012b).…”
Section: Social Information Experience and Speech Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linguistic experience also plays a role in the perception of ethnic varieties. In the New Zealand context, for example, high previous exposure to the Māori English variety has been shown to have a beneficial effect on perception and accuracy in ethnolect identification tasks even when listeners only have access to suprasegmental information in the speech signal, such as rhythm (Szakay, 2008a), intonation (Szakay, 2008b), and voice quality (Szakay, 2012b).…”
Section: Social Information Experience and Speech Perceptionmentioning
confidence: 99%
“…Māori English GOAT-monophthongization (Maclagan et al, 2008b) appears to be a recent innovation that Warren and Bauer (2004) do not yet mention in their survey of Māori English, but is unlikely to be affected by contemporary phonological patterns in Māori. Listeners are aware of these differences between the two codes, at least insofar as they are able to identify ethnic identify from auditory stimuli (Szakay, 2012b).…”
Section: 3mentioning
confidence: 99%
“…as [20] did for speakers of Standard Southern British English); another is to extract acoustic measures like spectral tilt, from which the degree of perceptual 'creakiness' (and 'breathiness') can be inferred (e.g. as [21] did for speakers of New Zealand English). Such studies are not included in this review because they do not offer an answer to the question what is the prevalence of creaky voice in English?…”
Section: Analysis/reporting Criteriamentioning
confidence: 99%
“…' Foulkes, Docherty, Khattab, and Yaeger-Dror (2010) found that listeners' identification of Tyneside children's gender was affected by two continuous measures (amplitude and F0) as well as several categorical measures; however, the authors also report significant correlations between amplitude and F0 in stimuli, suggesting potential issues with collinearity in the modeling procedure. In terms of voice quality, Szakay (2012) found that in New Zealand, ethnic identification was affected by several continuous voice quality measures; speakers with higher mean H1-H2 (a measure of creakiness) were likelier to be identified as Māori.…”
Section: Incrementality In Intonation and Perceptionmentioning
confidence: 99%